FULL FACTORIAL EXPERIMENTAL DESIGN AND COMPUTER SIMULATION APPLIED TO SHELL AND TUBE HEAT EXCHANGER SETUP - Lopes, P. H. S.; Rodrigues, A. P. C.; Cardoso, A. O.; Da Silva, J. V. W. (Revista de Engenharia Térmica, 2024)
In the operation of heat exchangers there are some variables to be controlled, making it difficult to found optimized parameters. The aim of this study was to compare the experimental and simulated values of the outlet temperatures, as well as to understand the influence of operating variables for the equipment. It was used a shell and tube heat exchanger didactic module, with a constant cold fluid flow rate equal to 1.4 L.min 1. The experiments were carried out on the basis of a 2² full factorial experimental design with central points, as well as computer simulations in the steady state and transient regime. The higher values for heat exchange overall heat transfer coefficient determined was around 250 W.m 2.K 1. Thus, the flow regime affects the evaluated response. In addition, the computer simulation in the permanent regime presented less relative deviation. Therefore, it can be seen that although the simulations show results close to the experimental ones, there are still associated errors that should be studied and minimized, since factors such as bubble formation were not considered in the simulations. Thus, it was found that computer simulations can be used to understand the operation of heat exchangers, but they are limited to real phenomena that are not considered in theoretical mathematical models. Therefore, this study elucidates the application of statistical and computer-assisted methods as a tool to comprehend heat exchangers behavior for industrial and didactic purposes.